The dagger X - Eames, Brian (Eames, Brian. Dagger chronicles., 2013)
Twelve-year-old Kitto Quick, stranded with his stepmother, Van, a Wampanoag girl, and a baby rescued from a slave ship on the very island where Morris hid valuable spices, learns powerful secrets of his past.